2000
DOI: 10.1103/physrevlett.85.622
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanics of Individual Carbon Nanotubes from Pyrolytically Grown Arrays

Abstract: The bending modulus of individual carbon nanotubes from aligned arrays grown by pyrolysis was measured by in situ electromechanical resonance in transmission electron microscopy (TEM). The bending modulus of nanotubes with point defects was approximately 30 GPa and that of nanotubes with volume defect was 2-3 GPa. The time-decay constant of nanotube resonance in a vacuum of 10(-4) Torr was approximately 85 micros. A femtogram nanobalance was demonstrated based on nanotube resonance; it has the potential for me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
118
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 187 publications
(130 citation statements)
references
References 13 publications
11
118
0
Order By: Relevance
“…Using a similar approach, Gao et al [37] have been able to measure mechanical properties of individual carbon nanotubes. In this case, a transmission electron microscopy (TEM) specimen holder was specially built for applying a voltage across the nanotube and its counter electrode so that the measurements can be done on a specific nanotube whose microstructure is determined by TEM.…”
Section: © 2002 Iupac Pure and Applied Chemistry 74 1753-1772mentioning
confidence: 99%
“…Using a similar approach, Gao et al [37] have been able to measure mechanical properties of individual carbon nanotubes. In this case, a transmission electron microscopy (TEM) specimen holder was specially built for applying a voltage across the nanotube and its counter electrode so that the measurements can be done on a specific nanotube whose microstructure is determined by TEM.…”
Section: © 2002 Iupac Pure and Applied Chemistry 74 1753-1772mentioning
confidence: 99%
“…More specifically, Poncharal et al observed effective bending moduli in the GPa range for 20-40-nm-diameter multiwall carbon nanotubes (MWNTs) grown by an arc discharge method [23]. However, the same group then observed effective bending moduli as low as -GPa in structurally imperfect MWNTs produced by precursor pyrolisis, and concluded that point and volume defects played a dominant role in the reduction of the overall bending modulus [24]. Deformation of the tube cross section is also expected to lower the position of resonance in these fibers.…”
Section: Resultsmentioning
confidence: 99%
“…The position of contact from the end of the fiber L was measured via an internal optical microscope in the AFM. We have also determined the spring constants of the PEDOT cantilevers by the resonancefrequency method, which is technically simpler than the AFM method [33]. To measure the resonance frequency of a PEDOT fiber, we position this single PEDOT cantilever ~10 m from an Au counterelectrode.…”
Section: Experimental Methodsmentioning
confidence: 99%